Simultaneous Determination of Isoniazid and Hydrazine by Spectrophotometric H-Point Standard Addition Method - KARIMI, M.A.; BEHJATMANESH-ARDAKANI, R.; BANIFATEMEH, F. (Asian Journal of Chemistry, 2010)
A new, simple, inexpensive and sensitive method for the simultaneous microdetermination of hydrazine and isoniazid has been developed. The H-point standard addition method was applied to the simultaneous determination of hydrazine and isoniazid. The method is based on the difference between the rates of their hydrazone formation with 4-dimethylaminobenzaldehyde. The experimental parameters, such as temperature and concentrations of 4-dimethylaminobenzaldehyde, sodium dodecyl sulfate and acidity were optimized to minimize the errors. The linear ranges of hydrazine and isoniazid were 0.01-1.0 and 1.0-80.0 μg mL-1, respectively. The detection limits for hydrazine and isoniazid were 0.005 and 0.8 μg mL-1, respectively. The proposed method was successfully applied to the simultaneous determination of hydrazine and isoniazid in several commercially available isoniazid formulations and satisfactory results were obtained.